Demand for Equity Stock Investment: A Focus on Nigeria Stock Exchange Market - Jude Chidi Onyenama (International Journal of Management and Business Intelligence, 2023)
The purpose of this is to examine those variables that determine investors demand for equity stock in the Nigeria stock market special attention was given factors such as earnings, dividends and net asset value. This study is a descriptive survey research aimed at investigating and to provide information on what influence the Nigerian equity stock investors in the Nigerian’s stock exchange of the Nigerian capital market. Data have been collected from the Nigerian stock exchange market, the annual reports and statement of accounts of sample and several issues of business times. The hypothesis formulated has been tested at both 1% and 5% significance levels using the F-statistics of regression model. This may have jointly and severally the independent variables have a significant relationship with investment demand. From the conclusion, recommendation such as tune element indicates the rate of change of these variables overtime and encouraging companies to participate in the stock market which will enhance future activities of the Nigeria capital market.